Mental health challenges of lesbian, gay, bisexual and transgender people: An integrated literature review - Moagi, Miriam M.; Der Wath, Anna E. van; Jiyane, Priscilla M.; Rikhotso, Richard S. (Health SA = SA Gesondheid, 2021)
Lesbian, gay, bisexual and transgender (LGBT) individuals are often stigmatised and discriminated against. This population is expected to experience poorer mental health outcomes compared with heterosexual and cis-gendered people, a phenomenon healthcare providers need to take note of and act upon. This study aimed to explore and describe the mental health challenges of LGBT people. An integrative literature search was conducted. The following electronic databases were searched: Academic Search Premier, Africa-Wide Information, Business Source Premier, eBook Collection (EBSCOhost), E-Journals, ERIC, Family & Society Studies Worldwide, Health Source: Nursing/Academic Edition, Humanities Source, MasterFILE Premier, MEDLINE, PsycARTICLES, Social Work Abstracts, TOC Premier, WorldCat.org, Taylor and Francis Journals, Biomed Central and Wiley Online Library. An internet search was also carried out using Google and Google Scholar databases. The following search terms were identified: 'LGBT' OR 'LGBT community' AND 'mental health challenges/problems' OR 'mental/psychiatric illness'. The reviewed literature comprised research conducted globally between 2010 and 2019. From the 2545 titles, 345 abstracts were examined, resulting in 57 articles. The 57 full-text articles were examined to verify whether they addressed the scope of the literature review, of them, 21 addressed the mental health challenges of LGBT people. Lesbian, gay, bisexual and transgender people experience the following mental health challenges: emotional distress, stigmatisation, victimisation, discrimination and barriers to accessing healthcare services. The results showed that although LGBT has been legalised in many countries, LGBT communities still experience significant mental health challenges. Healthcare providers are in a position to address challenges related to social and healthcare structures and act as advocates in order to promote the mental health of LGBT individuals.